Industrial Wireless Automation: Overview and Evolution of WIA-PA. Issue 10 (2018) - Neves Valadão, Yuri das; Künzel, Gustavo; Müller, Ivan; Pereira, Carlos Eduardo
Abstract: New wireless technologies for industrial applications are emerging, which are simple to install and maintain and can enable complex processes with security and reliability. In 2011, the Chinese Industrial Wireless Alliance developed an industrial wireless sensor network system called Wireless Networks for Industrial Automation and Process Automation, which will also attend Factory Automation. This paper intends to clarify the operation of these wireless systems, as well as to provide an overview of some of its evolution. In addition, some of the current equipment applied in WIA-PA and a few applications related to this technology are presented.